Editorial: on evidence and knowledge - Snyman, Gerrie 19XX- (Old Testament essays, 2017)
The recent publication and subsequent withdrawal of an incendiary blog in Huffington Post SA because of a lack of verification of its author or statistical claims in the blog, underscores an issue relevant to scholarship in general and to Old Testament Studies in particular: the construction of valid arguments and the use of evidence for these constructions as well as the eagerness to publish material in line with a particular ideology.